Mortality occurrence and morbidity trends in South Africa’s traditional initiation schools - Rathebe, Phoka; Malibongwe, Silinda; Mapungwana, Pheyiye (Orapuh Journal, 2025)
Introduction Traditional initiation schools in South Africa, particularly among the Xhosa community, serve as important cultural rites of passage for young males. However, despite their cultural significance, these practices have been associated with serious health risks, including high levels of morbidity and mortality. Reports over the years reveal persistent challenges related to unsafe surgical procedures, inadequate medical supervision, and adverse environmental conditions. Purpose The purpose of this study is to critically analyse the health outcomes linked to traditional initiation practices, with a particular focus on morbidity, mortality, and the broader public health implications. The study also seeks to highlight gaps in regulatory oversight and cultural factors that influence the persistence of harmful practices. Methods A mixed-methods approach was employed. The study reviewed 160 peer-reviewed articles and 150 media reports published between 2000 and 2024. Academic sources were identified through structured database searches, while media reports were selected from reputable national outlets. Data were synthesised using thematic analysis for qualitative sources and descriptive analysis for quantitative data. Studies relating to morbidity, mortality, and health system responses were included in the final review. Results The findings reveal alarming health trends, with an estimated 400 reported deaths and numerous cases of infections, dehydration, and genital amputations. Most incidents occurred in remote areas where initiation schools operate without proper medical oversight. Cultural resistance to modern health interventions further complicates efforts to improve safety practices. Additionally, the psychological effects on initiates—including trauma and long-term mental health challenges—are frequently neglected in public discourse. Government interventions have yielded limited success due to tensions between traditional authority structures and regulatory attempts. Conclusion Traditional initiation practices remain deeply embedded in cultural identity, yet they continue to expose young males to preventable health risks. This study underscores the urgent need for comprehensive regulatory frameworks that incorporate cultural sensitivity while ensuring safety. Strengthened collaboration between traditional leaders, health professionals, and government bodies is essential to safeguard the well-being of initiates. Ultimately, the rites of passage must be preserved in ways that uphold both cultural heritage and the health and dignity of young men.